Land-Use Type Drives Soil Population Structures of the Entomopathogenic Fungal Genus Metarhizium - María Fernández-Bravo; Florian Gschwend; Johanna Mayerhofer; Anna Hug; Franco Widmer; Jürg Enkerli (Microorganisms, 2021)
Species of the fungal genus Metarhizium are globally distributed pathogens of arthropods, and a number of biological control products based on these fungi have been commercialized to control a variety of pest arthropods. In this study, we investigate the abundance and population structure of Metarhizium spp. in three land-use types—arable land, grassland, and forest—to provide detailed information on habitat selection and the factors that drive the occurrence and abundance of Metarhizium spp. in soil. At 10 sites of each land-use type, which are all part of the Swiss national soil-monitoring network (NABO), Metarhizium spp. were present at 8, 10, and 4 sites, respectively. On average, Metarhizium spp. were most abundant in grassland, followed by forest and then arable land; 349 Metarhizium isolates were collected from the 30 sites, and sequence analyses of the nuclear translation elongation factor 1α gene, as well as microsatellite-based genotyping, revealed the presence of 13 Metarhizium brunneum, 6 Metarhizium robertsii, and 3 Metarhizium guizhouense multilocus genotypes (MLGs). With 259 isolates, M. brunneum was the most abundant species, and significant differences were detected in population structures between forested and unforested sites. Among 15 environmental factors assessed, C:N ratio, basal respiration, total carbon, organic carbon, and bulk density significantly explained the variation among the M. brunneum populations. The information gained in this study will support the selection of best-adapted isolates as biological control agents and will provide additional criteria for the adaptation or development of new pest control strategies.